A Social Norm Nudge to Save More: A Field Experiment at a Retail Bank - Robert Dur; Dimitry Fleming; Marten van Garderen; Max van Lent (Center for Economic Studies and Ifo Institute (CESifo), 2021)
A large fraction of households have very little savings buffer and are therefore vulnerable to financial shocks. This paper examines whether a social norm nudge can induce such households to save more. We ran a large-scale field experiment at a retail bank in the Netherlands. We find that households who are exposed to the social norm nudge click more often on a link to a personal web page where they can start or adjust an automatic savings plan. However, analyzing detailed bank data, we find no treatment effect on actual savings, neither in the short run nor in the long run. Our null findings are quite precisely estimated. A complementary small-scale survey experiment suggests that people did notice the social norm nudge and also that it had an impact on savings intentions.
Keywords: C93; D14; D90; E21; G40; 330; household savings; field experiment; nudges; social norms